VD_FINDINFO Jug / 2025 / 228 vom 23. August 2024 - VD Tribunal cantonal (2024)
PRÉSOMPTION D'INNOCENCE, REJET DE LA DEMANDE, INDEMNITÉEN GÉNÉRAL, LÉGITIME DÉFENSE, FRAIS JUDICIAIRES | 15 CP, 10 CPP (CH), 426 al. 2 CPP (CH)